Static Analysis of Structural Structure of Vertical Wind Tunnel (VWT) Design By Catia V5R21 - Muhamad Jalu Purnomo (Jurnal Teknik Mesin, 2018)
Vertical Wind Tunnel (VWT) is a wind tunnel application that is directed vertically upwards, so that the air impulse is applied as an alternative to people (athletes) feeling the sensation of flying, like parachuting when jumping at altitude out of an airplanea. VWT will certainly reduce the potential for accidents, improve the efficiency of skydiving, and improve the quality of skydiving athletes. To ensure the design of the VWT structure is safe, it is necessary to test the strength of the structure with load = 55212.16 Newton and load thrust = 46826.3516 Newton. VWT structure uses 2 types of steel material, namely the type of Steel A36 and Steel A441 because this type has the appropriate material property other than that it is very easy to get on the market. then simulated using CATIA V5R21 software. So that the obtained value of Steel A36 Margin of Safety (MS) is 2.79 (load) and 3.48 (load thrust). For Steel A441, the MS value is 4.52 (load) and 5.51 (load thrust), from all the two materials producing an MS value> 1, indicating that the design of the VWT structure is said to be safe.